The Implementation of Therapeutic Community (TC) in Behavioral Change Formation among Beneficiaries with Substance Abuse Problems at Sentra Galih Pakuan - Zakiyyah Balqizh Ridwananda; Sahadi Humaedi; Nunung Nurwati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Substance abuse is one of the social problems that requires special attention and intensive intervention. This problem can be addressed through participation in social rehabilitation programs, one of which is the therapeutic community (TC) approach. The implementation of the therapeutic community (TC) approach at the primary stage in Sentra Galih Pakuan is carried out through the utilization of the community structured activities, and the application of four structures in shaping behavioral changes among beneficiaries. This study employed a descriptive qualitative method, with data collected through interviews, documentation studies, and literature studies. The result of the study indicate that the community within the therapeutic community functions as a medium for behavioral development through social relationships and the active participation of beneficiaries in activities. The existence of various structured activities also becomes part of psychosocial therapy in providing social learning for beneficiaries. In addition, Sentra Galih Pakuan implements four structures that support the social rehabilitation process within the therapeutic community approach.